1α, 25(Oh)2Vitamin D3-Regulated Expression of the Eukaryotic Genome. (8th October 2014) - Hannah, Steven S.; Norman, Anthony W.
Abstract : 1α, 25(OH)2 vitamin-D3, [1α, 25(OH)2 D3 ] is a potent steroid hormone that produces a wide array of biologic effects in a variety of target tissues within the body through its ability to modulate gene transcription of specific target genes. Evidence for transcription regulation of a specific gene typically includes 1α, 25(OH)2 D3 -induced modulation in mRNA levels. Additionally, evidence may include measurements of transcription and or the presence of a vitamin D response element within the promoter region of the gene. To date, over 50 genes have been reported to be transcriptionally regulated by 1α, 25(OH)2 D3 - We present a current list of these genes and the evidence supporting their inclusion on the list.